Copernicus and Copernicans: Galileo, Kepler, Bruno - Çimen, Ünsal (Polish Academy of Arts and Sciences,Commission on the History of Science, 2024)
Copernicus claimed the Earth revolves around itself and the Sun. He also claimed that the universe was finite and that no intelligent life existed on other planets. Galileo and Kepler shared these claims; therefore, they deserve to be called Copernicans. But what about Giordano Bruno? He adopted Hermetic philosophy and opposed Copernicus’s mathematical (geometric) method; he also claimed, unlike Copernicus, that the universe was infinite and that there were intelligent life forms on other planets. So, can we define Bruno and those who thought like him as Copernicans? Ernan McMullin answers this question in the negative. In this paper, I will argue that the differences between Bruno and Copernicus mentioned by McMullin cannot be used as criteria for claiming that Bruno and others who thought like him were not Copernicans; instead, I argue that believing the Earth rotates around itself and the Sun should be considered sufficient to call someone a Copernican. © 2024, Polish Academy of Arts and Sciences,Commission on the History of Science. All rights reserved.
Kopernik i kopernika?czycy: Galileusz, Kepler, Bruno
Keywords: anthropocentrism; Copernicus; geocentrism; Giordano Bruno; heliocentrism